Public Management: Ertüchtigte Staatlichkeit vor dem Hintergrund des politischen Paradoxons - Ulrich Klüh (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2021)
How can we toughen up the state against the backdrop of the transformative challenges of climate change, planetary boundaries, and technological progress? I examine this question through a fundamental analysis of the dimensions of democratic politics and the "management" of public affairs. I argue that the state's ability to act is suffering from the withering away of the antagonistic dimension of democratic politics. At the same time, the state itself often puts on too tight a corset by narrowing its financial leeway and providing central public management organizations with a considerable degree of independence that was not secured by a similarly developed system of public accountability.
Keywords: H1; H7; G2; P1; P43; 330; Socio-ecological transformation; climate change; statehood; governance